NILAI SOSIAL DALAM NOVEL MAKHLUK BUMI KARYA SAYAKA MURATA - Ufan koliwora; Marwati; Fahruddin Hanafi (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe the social values contained in the novel Makhluk Bumi by Sayaka Murata. This study is expected to provide the following benefits. 1) provide readers with an understanding of literary works regarding the description of social values in the novel Makhluk Bumi by Sayaka Murata. 2) as a contribution of information for those conducting research on social values in the novel Makhluk Bumi by Sayaka Murata. 3) add to literary studies by applying the theory of the sociological approach to literature in the novel. The method used is a qualitative descriptive method. This type of research is a type of literature. The source of this research is the text of the novel Makhluk Bumi by Sayaka Murata with a total of 264 pages, published by Gramedia Pustaka Utama in Jakarta in 2025. Data collection was carried out using reading techniques and note-taking techniques. In this study will be analyzed using a sociology of literature approach. This novel contains social values with the title of the novel Makhluk Bumi by Sayaka Murata, namely: 1) The value of harmony, 2) the value of caring, 3) the value of politeness, and 4) helping each other.